ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PENGGUNA UNTUK MENDORONG PENGGUNAAN OPEN SOURCE SOFTWARE DAN IMPLIKASI MANAJERIALNYA - Erry Ricardo Nurzal; E. Gumbira Sa’id; Heny K. Daryanto; Hartoyo Hartoyo (Jurnal Manajemen & Agribisnis, 2010)
This study has two objectives namely (1) To measure the acceptance of Open Source Software, (2) To determine whether OSS quality, OSS availability, personal innovativeness, gender, income, social influence, cultural affinity and type of university influence users using or not using Open Source Software.Data used in this research were primary data. The data collected were data from informatic engineering or computer science students using OSS in Bogor Agricultural University, Bandung Institute of Technology, University of Indonesia, University of Gunadarma, University of Bina Nusantara and University of Budi Luhur. Questionnaire was used to collect the data. Sampling technique was done randomly.The study results show that students accepting OSS were 77,6 % and students not accepting OSS were 22,4 % at the state university groups. Meanwhile, students accepting OSS were 49,9 % and students not accepting OSS were 50,1 % in the private university groups.. External factors directly influencing users for using Open Source Software were personal innovativeness, income and status of university. Moreover,   external factors indirectly influencing users for using or not using Open Source Software were OSS quality, OSS availability, personal innovativeness, gender, cultural affinity and  status of university.